Evaluation of altered pyroclastics from Rhodope prefecture, Thrace, Greece as constituents of pozzolanic cements - ΜΑΡΑΝΤΟΣ Ι.; ΚΟΣΙΑΡΗΣ Γ.; ΠΕΡΔΙΚΑΤΣΗΣ Β.; ΚΑΡΑΝΤΑΣΗ Σ.; ΚΑΛΟΕΙΔΑΣ Β.; ΜΑΛΑΜΗ Χ. (Bulletin of the Geological Society of Greece, 2001)
In the Komotini Tertiary basin, tuffs of various types are alternated with tuffites, siltostones, sandstones and marls forming a thick volcanosedimentary sequence. The tuffs are characterised as ash-, fine ash- and in some cases as welded ash tuffs. Crystal-,lappili- and breccia tuffs also occur. The tuffs are built up of glass shards, pumice shards and crystal fragments which are cemented by glassy material. Crystal fragments are represented by quartz crystals. Plagioclase, albite, sanidine and biotite exist as well. Essentially, the vitric parts of the tuffs are altered to zeolites (heulandite 2 and/or mordenite, analcime, laumontite / scolecite), clay minerals (smectite, kaolinite +/or mixed layer I/S of regular type), Si02 minerals (quartz, cristobalite) and K-feldspar. For the purposes of this study, firstly, standard portland cement concrete specimens and concrete specimens with pyroclastic material from three different places, replacing portland cement by 20%, were prepared. The mineralogical composition of the samples under study and the area where they come from, is as follows: a. Iampolis: analcime + quartz + K-feldspar + albite + Illite/Smectite b. Darmeni : analcime + quartz + K-feldspar + albite + calcite c. Skaloma : smectite + cristobalite + heulandite-2 + mordenite + K-feldspar + quartz The compressive strength of the prepared specimens after periods of 7 and 28 days was measured and the pozzolanic activity of the samples was calculated according to ASTM Standard C618. Following the first test, the pozzolanic activity of a second sample from Iampolis area was more extensively studied. The compressive strength of concrete specimens made of 100% Portland cement of 145 type, and concrete specimens that were prepared by replacing Portland cement in proportions of 10, 20, 30 and 40% was determined. From the results of this study it is concluded that the analcimic tuffs could be a potential source for pozzolanic cement. More extensive study is needed for the estimation of the percentage of the altered pyroclastics that gives the optimum results concerning the cement pozzolanic activity. The optimization of the pozzolanic properties of the altered pyroclastics by calcination may be investigated as well.